Use of amino acids for a highly efficient somatic embryogenesis in grapevine `Crimson Seedless' - Nookaraju, A.; Agrawal, Dinesh C. (Vitis, 2013)
Somatic embryogenesis influenced by growth regulators and amino acids was studied in in vitro leaves of grapevine `Crimson Seedless'. In vitro leaves of the cultivar were collected from multiple shoot cultures maintained on Murashige and Skoog's (MS) basal medium supplemented with 9 mu M N-6-benzyladenine (BA). Among the growth regulators used, BA at 4.5 mu M induced higher embryogenic response producing more number of somatic embryos per explant. This response was increased with the addition of 5 mu M naphthoxyl-acetic acid (NOA) to 1/2 MS containing 4.5 mu M BA. Further, supplementation of amino acids in the callus induction medium significantly improved the embryogenic response of in vitro leaves. The higher number of explants showing somatic embryo production (55.3 %) and higher number of somatic embryos per explant (15.5 per explant) were recorded with the supplementation of 5 mM phenylalanine to callus induction medium. Primary somatic embryos showed repetitive embryogenesis on % MS medium devoid of growth regulators. Plantlets derived from somatic embryos were transferred to soil-sand-peat mixture (1:1:1 v/v) and hardened plantlets were established in greenhouse with 90 % survival. This somatic embryogenesis system has been successfully used for Agrobacterium-mediated transformation studies in `Crimson Seedless' in our laboratory. To our knowledge, this is the first report on the use of amino acids for the high efficient somatic embryogenesis in grapevine.
Keywords: Amino acids; somatic embryogenesis; Vitis vinifera L.; `Crimson Seedless'